Metode Storytelling Papeda Dalam Meningkatkan Pengetahuan dan Apresiasi Masyarakat Rantau Dari Timur - Lyly Soemarni Lioe (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2023)
Purpose : This study aims to determine the influence of storytelling methods on the appreciation of overseas communities from the east on papeda food with an evaluative descriptive design. The design used is one group design pre-test-post-test.Methods : The total sample was 57 respondents. online through Google Form, the author distributed a questionnaire link starting from June 26 to July 10 2022.Implications : The results of this study obtained pre-test appreciation of respondents reaching a total score of 1-5, namely the category of less appreciation for papeda amounting to 35 people (61.4%), and those who reached a total score of 6-9, namely the category of good appreciation of papeda totaling 22 people (38.6%), while the post-test appreciation was found that all respondents reached a total score of 8-14, namely the category of good appreciation for papeda amounting to 57 people (100.0%).     Keywords: Storytelling, Appreciation, Papeda